Upaya Perawatan Integritas Kulit Pada Pasien Stroke - Maskun, Alfi Lailiatus Zahroh; , Dian Hudiyawati, S.Kep.,Ns., M.Kep (2017)
Background : Stroke prevalency in the world according the data of WHO in about 20,5 million peoples. According to Dinkes in Central Java Provincy in yeaar 2012, stroke prevalency about 0,07% higher than in the year 2011 about 0,03%. Decubitus prevalency which is reported in each home around 12,9% to 19%, and in Indonesia has been reported about 25% persons committed decubitus. Decubitus is referred to such an illness or skin destruction caused by over stressing, so tha make the effect of sirculation disruption. Decubitus must be handled soon from every medical forces potientially causing for such more complication like absecity, osteomielitis, bakteremia and fistula. This main action can be done by a nurses, using non pharmacology therapy, example : reposition for about 2-3 hours in a day. Objective : the author purpose can provided an overview of nursing care for diagnosing the skin integrity damage for patients who are committed stroke. Methods : the author has made research using descriptive method with care study approach in HCU rooms on february 17-19 2017. Steps which are passed : collecting the data, analyzing data, making medical care diagnosis, making intervension, doing the care action, and making care evaluation. Result : after making many care action for 3x24 hours, it is suggested that the skin integrity damage will be better with some of the acts like assessing the disease according to the characteristic of disease, treatment for the disease, giving lotion or oil, massaging, and reposition 2-3 hours a day. Those action makes the effect on the process of recovering the disease. Summary : the problems of skin damage can be solved half way so that it needs more interventions to reach the criteria of results which is made to be happen.